13.3k views
0 votes
(100 points) Can someone help me understand how to solve this problem? Not just the answer to the problem but the process too please. Thank you!

(100 points) Can someone help me understand how to solve this problem? Not just the-example-1
User Dan Shield
by
5.4k points

1 Answer

4 votes

Answer:


\displaystyle (3x+4)/((x-5)(x-1)) = (19)/(4(x-5)) +(-7)/(4(x-1))

Explanation:

We are given the rational expression:


\displaystyle (3x+4)/(x^2 -6x +5)

And we want to find two rational expressions that sum to the above expression.

This technique is known as partial fraction decomposition. First, factor the denominator into linear factors:


\displaystyle = (3x+4)/((x-5)(x-1))

Let A and B be two unknown constants. We can let:


\displaystyle (3x+4)/((x-5)(x-1)) = (A)/(x-5) + (B)/(x-1)

Find A and B. Multiply the entire equation by the denominator:


\displaystyle \displaystyle (3x+4)/((x-5)(x-1))\left((x-5)(x-1)\right) = \left((A)/(x-5) + (B)/(x-1)\right)\left( (x-5)(x-1)\right)

Simplify:


3x + 4 = A(x-1) + B(x-5)

To find A and B, let x equal some value such that it will cancel out one variable. First, let x = 1. Then:


\displaystyle 3(1) + 4 = A((1) - 1) + B((1) -5)

Simplify:


\displaystyle 7 = A(0) + B(-4) \Rightarrow -4B = 7

Hence:


\displaystyle B = -(7)/(4)

To find A, let x = 5 (we choose this value because it allows us to cancel B):


\displaystyle 3(5) + 4 = A((5)-1) + B((5) - 5)

Simplify:


\displaystyle 19 = A(4) + B(0) \Rightarrow A = (19)/(4)

We had:


\displaystyle (3x+4)/((x-5)(x-1)) = (A)/(x-5) + (B)/(x-1)

Substitute:


\displaystyle (3x+4)/((x-5)(x-1)) = ((19)/(4))/(x-5) +(-(7)/(4))/(x-1)

In conclusion:


\displaystyle (3x+4)/((x-5)(x-1)) = (19)/(4(x-5)) +(-7)/(4(x-1))

User Squirrelkiller
by
5.7k points